Analisis Penerimaan Pengguna Terhadap Aplikasi Jiwa+ Menggunakan Metode UTAUT 2: Studi Kasus pada PT Mega Group Indonesia - Shidqi, Farsya Lisanush; Utami, Dwi Yuni (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to examine the influence of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit on behavioral intention, as well as the effect of behavioral intention and habit on use behavior in the context of the Jiwa+ application used by Janji Jiwa consumers. A quantitative approach was employed by distributing questionnaires to 100 respondents who are users of the Jiwa+ application under PT Mega Group Indonesia. Data were analyzed using multiple linear regression based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) framework. The results show that habit and social influence significantly affect behavioral intention, while other variables do not have a significant impact. Furthermore, habit and behavioral intention positively influence use behavior. These findings suggest that digital application developers in the food and beverage sector should prioritize habit formation and leverage social influence to enhance technology adoption among users.